Effiziente Prozesskettenauslegung für das Umformen lokal wärmebehandelter und geschweißter Aluminiumbleche - Staud, Detlev (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)
The scope of this work was the generation of basic principles to the efficient forming process design of local heat treated and welded aluminum sheet metal. The main process characteristic is a selective heat treatment to adapt the mechanical properties of unwelded or welded aluminum sheets for the subsequent forming process. The fundamental objective of the dissertation was the development of a simulation based process design by means of an inverse procedural method. In contrast to an ordinary approach the heat treatment layout is already determined within the forming step. Thus a robust forming process is generated before the heat treatment parameters are defined. The benefits of this inverse approach are less extensive simulations loops of both forming and heat treatment calculations. Supported are these investigations by means of relevant material properties and the continuous validation of the heat treatment and the forming proces